L’intention entrepreneuriale chez les étudiants : Une étude exploratoire des déterminants - RETAL, Fatiha (Revue Internationale du Chercheur, 2025)
Abstract The analysis of entrepreneurial intention is located in upstream of the entrepreneurial behavior. This research is part of this framework, it aims to study the impact of factors linked to attitudes associated with behavior, subjective norms and perceptions of behavioral control on the entrepreneurial intention of students. Theoretically, this article is based on the theory of planned behavior (Ajzen, 1991) and the model of entrepreneurial intention (Tounes, 2006). In terms of methodology, we adopted an exploratory qualitative methodology through semi-structured interviews conducted with a sample of 13 students and entrepreneurs at the national level. The research results show that our analysis model is validated in the Moroccan student context. Additionally, the active participatory teaching approaches, the teacher’s posture and students’ engagement in extracurricular activities have a significant impact on the entrepreneurial intention of students.